The Supervision Management Process of Deep Learning Islamic Education with a Love-Based Curriculum in Elementary Schools - Ayu Sofya; Ahmad Zainuri (Examinations: Jurnal Pendidikan Guru Sekolah Dasar, 2025)
This study aims to examine the process of Islamic educational supervision management based on deep learning within a love-based curriculum at the elementary school level. Islamic educational supervision plays a crucial role in improving the quality of learning that is not only oriented toward academic achievement but also toward the development of students’ character and moral values. This research employed a qualitative descriptive approach using library research. Data were collected through an in-depth review of books and scholarly journal articles related to Islamic educational supervision, deep learning, and love-based curriculum. Data analysis was conducted using content analysis techniques to identify patterns and conceptual relationships among the studied themes. The findings indicate that well-planned, humanistic, and collaborative Islamic educational supervision effectively supports the implementation of deep learning and a love-based curriculum. Supervision contributes to enhancing teachers’ professionalism, fostering a positive school culture, and creating a safe and conducive learning environment. The integration of deep learning and a love-based curriculum through Islamic educational supervision is considered an effective strategy for realizing holistic Islamic education in elementary schools.